PEMBINAAN OLAHRAGA TENIS LAPANGAN MELALUI ASPEK BIOMEKANIK DAN KINESIOLOGI - Nurkadri Nurkadri; Samira Samira; Rahmad Dame; Joshua Sitompul; Theresia Marpaung; Tuahta Mario Eka Putra Pubra; Hasanul Arifin; Putri Rahmadani Lubis (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
In the game of tennis there are many factors that must be mastered by the players, because when viewed from the movement, the sport of tennis is a tough sport, so to be able to play tennis properly and be able to maintain the shape of the game there are several basic factors that a tennis player needs to have. This research is a descriptive qualitative research by describing and analyzing service in tennis coaching through biomechanical and kinesiological aspects. The steps taken are articles, data reduction, data analysis, data compilation, and drawing conclusions. Article preparation is done by collecting articles from various online sources with relevant topics. This research is a collaborative research that is practical based on the problems that occur in the development of tennis sports. Thus it can be said that a coach or sports coach must be able to establish good communication and be able to give an appropriate assessment of what is being done and what has been done and be able to provide feedback. Recognizing the importance of the role of a coach in the achievement of athletes, a coach must work professionally.